Photonics, plasmonics and information optics : research and technological advances - Deyasi, Arpan, 1978-; Debnath, Pampa, 1981-; Datta, Asit Kumar; Bhattacharyya, Siddhartha, 1975- (Boca Raton : CRC Press, 2021)
This edited volume covers technological developments and current research trends in the field of photonics, plasmonics and optics, focusing on photonic crystals, semiconductor optical devices, optical communications and optical sensors, with an emphasis on practical sectors. It broadly contains the latest research domains contributed by experts and researchers in their respective fields with a major focus on the basic physics. Works in the area of electromagnetic bandgap structures (EBG) and metasurfaces are included for applications in different aspects of communications systems. Further, it covers research phenomena of microwave photonic devices to develop miniaturized high-frequency devices. FEATURES Reviews nonlinear optical phenomena related with materials and crystals and plasmonic effects on device fabrications Contains a detailed analysis on photonic crystals with their applications in making all-optical passive components Focusses on nonlinear optics, more precisely on crystals and materials, and computational aspects on evaluating their properties from Maxwell's equations Presents an extensive study on the physics of EBG structures for application in antenna and high-frequency communications Includes metamaterials and metasurfaces for applications in photonics as well as in microwave engineering for high-frequency communication systems Photonics, Plasmonics and Information Optics: Research and Technological Advances is aimed at researchers, professionals and graduate students in optical communication, silicon photonics, photonic crystals, semiconductor optical devices, metamaterials and metasurfaces, and microwave photonics.
1. Foundation, Progress and Future of Photonics, Plasmonics and Information Optics: Researchers Perspective [Pampa Debnath, Arpan Deyasi and Siddhartha Bhattacharyya] 2. Bandgap Engineering of Sol-Gel Spin-Coated TiO2 Thin Film on Glass Substrate [Soham Lodh and Rajib Chakraborty] 3. Metamaterials and Metasurfaces for High-Frequency Applications [Somak Bhattacharyya] 4. Design of Superlens Using 2D Photonic Crystal with Various Geometries under Polarized Incidence: Design of Superlens Using 2D Photonic Crystal [Moumita Banerjee, Pampa Debnath and Arpan Deyasi] 5. Investigation on Some Fast Optical/Opto-Electronic Switching Systems for Implementing Different Modulation Schemes [Minakshi Mandal, Suranjan Lakshan, Debashri Saha, Agnijita Chatterjee and Sourangshu Mukhopadhyay] 6. Slotted Photonic Crystal Waveguide: An Effective Platform for Efficient Nonlinear Photonic Applications [Mrinal Sen and Tanmoy Datta] 7. Performance Evaluation of Raman Amplifier-Embedded Optical Fibre Communication System at Both Minimum Dispersion and Minimum Attenuation Windows [Rajarshi Dhar and Arpan Deyasi] 8. Ultra-Narrowband Optical Comb Filter Using Sampled Fibre Bragg Gratings [Somnath Sengupta] 9. A Real-Time and Wireless Structural Health Monitoring Scheme for Aerospace Structures Using Fibre Bragg Grating Principle [Ahsan Aqueeb, Mijia Yang, Benjamin Braaten, Ellie Burczek and Sayan Roy] 10. Gap Solitons in Photorefractive Optical Lattices [Aavishkar Katti and Priya Singh] 11. Real-Time Numerical Analysis of Photonic Bandgap Structure Using Finite Difference in Time-Domain Method [Rajorshi Bandyopadhyay and Rajib Chakraborty] 12. Super Achromatic Multi-Level Diffractive Lens: A New Era Flat Lenses [Ekata Mitra and Subhashish Dolai] 13. Adaptive Repetitive Control of Peristaltic Pump Flow Rate with an Optical Flow Sensing System [Naiwrita Dey, Ujjwal Mondal and Anindita Sengupta] 14. Conclusion [Pampa Debnath, Arpan Deyasi and Siddhartha Bhattacharyya]
OCLC-licensed vendor bibliographic record.
Keywords: Photonics; Plasmonics; Fiber optics; TECHNOLOGY / Electricity; TECHNOLOGY / Lasers; TECHNOLOGY / Material Science